Banks' lending to public and private sectors and house prices: does bank ownership matter?. Issue 2 (25th June 2019) - Gholipour, Hassan F.; Oikarinen, Elias; Tajaddini, Reza
Abstract : Purpose: The purpose of this study is to examine the interaction between banks' lending to public and private sectors and house prices using data from the Iranian banking system including, commercial government-owned banks (CGBs), specialized government-owned banks and private banks. Design/methodology/approach: The authors use quarterly data from the second quarter of 2004 to the first quarter of 2016 and apply structural vector autoregression models. Findings: The results show that: a positive shock to the loan supply to the private sector triggers a positive response from house prices; a positive shock to the loan supply to the public sector does not trigger a positive response from house prices; house price appreciations contribute significantly to banks' lending to the public sector but not lending to the private sector; each loan supply by three different types of banks influences house prices positively; and CGBs' lending to the private sector does not respond to house price shocks. Originality/value: Although the relationship between banks' lending and house prices is well-established in the literature, existing studies have not yet examined whether bank ownership matters for the link between banks' lending and house prices.